English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

6 answers

X - 6X + 15 = 7 + 2X

8 = 7X

X = 8/7

2006-12-03 03:13:48 · answer #1 · answered by eVolution 2 · 0 1

I am in agreement with lastlife on this one and the proof is in the pudding.

(x - 3)(2x - 5) = 7 + 2x the first thing we gotta do is f.o.i.l. the left side
First, Outside, Inside, Last
first x(2x) = 2x^2
outside -3(-5) = 15
inside -3(2x) = -6x
last x(-5) = -5x combine like terms -5x-6x = -11x

now rewrite equation: 2x^2 -11x + 15 = 7 + 2x
-2x - 7 =-7 -2x
2x^2 -13x + 8 = 0 multiply through by -1

-2x^2 + 13x - 8 = 0 we now have the form ax^2 + bx + c = 0

quadratic equation x = -b + or - sqr(b^2 - 4ac)/2a

x= -13 + sqr(169 - 4(-2)(-8))/2(-2)
x= -13 - sqr(169 - 4(-2)(-8))/2(-2)

-4(-2 ) = 8(-8) = -64
2(-2) = -4

x= -13 + sqr(169 - 64)/-4
x= -13 - sqr(169 - 64/-4

169-64 = 105

x= -13 + sqr(105)/-4
x= -13 - sqr(105)/-4

The calculator on this computer is mysteriously missing and my scientific calculator is not handy. So all you have left is to calculate the square root of 105 wich should be 10 point something, then divide by -4 which will be a negative number. X will have two values one larger than the other but both on the negative side. Becauyse when you got to subtract a negative number from a negative number the subtracting number changes its sign -(-1) = 1.

my estimate of x values are x = -15.xxx and x = -10.xxx

2006-12-03 05:16:57 · answer #2 · answered by ikeman32 6 · 0 0

x-3(2x-5)=7+2x ; from here, distribute out the left side
2x^2-11x+15=7+2x ; then, bring all the terms to the left side
2x^2-13x+8=0 ; considering that this isn't factorable, utilize the quadratic formula
x= (-b+/-sqrt.(b^2-4ac))/2a
x=(13 +/- sqrt.(169-4(2)(8)))/2(2)
x=(13 +/- sqrt. 105)/4
in other words, 13 +/- the square root of 105, then that answer divided by 4; plug those two answers in to the part where the two equal each other, and viola
while the answer of 8/7 does satisfy the equation, so does my answer...i just took the long way around it

2006-12-03 03:24:41 · answer #3 · answered by Anonymous · 1 1

X - 3(2X - 5)= 7 + 2X
X - 6X + 15 = 7 + 2X
-5x + 15 = 7 + 2x
8 = 7X
X = 8/7

2006-12-03 03:14:10 · answer #4 · answered by sft2hrdtco 4 · 1 1

X - 3(2X - 5)= 7 + 2X
x-6x+15=7 + 2x

x-6x-2x=-15+7

-7x=-8

x=8/7

2006-12-03 03:14:02 · answer #5 · answered by Edward 7 · 0 1

develop second term at the left side -6X +15

Put at its place X - 6X +15 = 7+2X

Put the terms on X at the left, the others at the right

X -6X-2X = 7-15

-7X = -8 X =8/7

2006-12-03 03:16:28 · answer #6 · answered by maussy 7 · 0 1

fedest.com, questions and answers